Day 2 Tue, May 02, 2017 2017
DOI: 10.4043/27822-ms
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Coupling of Mooring and Riser Systems and FPSO Roll motions on the Design of Flexible Risers

Abstract: For the development of the new frontiers in Brazil, spread moored FPSOs with a large number of flexible risers connected to one board of the unit are considered. Due to the large water depth and severe environmental conditions, the design of the flexible risers is challenging and the roll motions of the FPSO are a key parameter. The roll motions may induce large vertical displacements at the top of the risers which affect the ultimate strength of the flexible pipe as well as fatigue of end- fittings. Moreover,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
0
2
2
Order By: Relevance
“…It can be seen that the added mass of the riser lines has the largest contribution, while the effects of damping and stiffness of the riser lines are smaller. This conclusion contradicts the finding by Rezende et al [9], who concluded that the damping effect of the riser was the most significant and the inertia term might be negligible. The FPSO model used in this study operates in a shallow water environment while the model studied by Rezende et al [9] operates in the deep sea environment.…”
Section: Results and Discussion 41 The Effect Of Asymmetric Riserscontrasting
confidence: 84%
See 3 more Smart Citations
“…It can be seen that the added mass of the riser lines has the largest contribution, while the effects of damping and stiffness of the riser lines are smaller. This conclusion contradicts the finding by Rezende et al [9], who concluded that the damping effect of the riser was the most significant and the inertia term might be negligible. The FPSO model used in this study operates in a shallow water environment while the model studied by Rezende et al [9] operates in the deep sea environment.…”
Section: Results and Discussion 41 The Effect Of Asymmetric Riserscontrasting
confidence: 84%
“…This conclusion contradicts the finding by Rezende et al [9], who concluded that the damping effect of the riser was the most significant and the inertia term might be negligible. The FPSO model used in this study operates in a shallow water environment while the model studied by Rezende et al [9] operates in the deep sea environment. As the damping effect of risers has a nature of quadratic drag, and also closely related to the dynamic line behavior, the increase in water depth and riser length may rapidly increase the damping level, thus making the effect of added mass relatively small.…”
Section: Results and Discussion 41 The Effect Of Asymmetric Riserscontrasting
confidence: 84%
See 2 more Smart Citations